Discrimination between Alkali Metal Cations by Yeast : II. Cation interactions in transport - Armstrong, W. McD. (The Rockefeller University Press, 1967)
K(+) is a competitive inhibitor of the uptake of the other alkali metal cations by yeast. Rb(+) is a competitive inhibitor of K(+) uptake, but Li(+), Na(+), and Cs(+) act like H(+). At relatively low concentrations they behave as apparent noncompetitive inhibitors of K(+) transport, but the inhibition is incomplete. At higher concentrations they inhibit the remaining K(+) transport competitively. Ca(++) and Mg(++) in relatively low concentrations partially inhibit K(+) transport in an apparently noncompetitive manner although their affinity for the transport site is very low. In each case, in concentrations that produce "noncompetitive" inhibition, very little of the inhibiting cation is transported into the cell. Competitive inhibition is accompanied by appreciable uptake of the inhibiting cation. The apparently noncompetitive effect of other cations is reversed by K(+) concentrations much higher than those necessary to essentially "saturate" the transport system. A model is proposed which can account for the inhibition kinetics. This model is based on two cation-binding sites for which cations compete, a carrier or transporting site, and a second nontransporting (modifier) site with a different array of affinities for cations. The association of certain cations with the modifier site leads to a reduction in the turnover of the carrier, the degree of reduction depending on the cation bound to the modifier site and on the cation being transported.